PENDAMPINGAN MASYARAKAT DALAM MONITORING EKOSISTEM LAMUN DI PANTAI MUTIARA, KABUPATEN SUMBAWA - Muh. Fahruddin; Anita Prihatini Ilyas; Davit Aldi (Universitas Mataram, 2023)
Kaung Island has the potential for seagrass ecosystems which are important ecosystems for the survival of various types of aquatic biota. Rahmawati et al., (2014) said that seagrass damage is caused by natural and human factors, especially those who are active in coastal areas. This is due to a lack of understanding and public awareness. As for the things that need to be done for the sustainability of seagrass ecosystems, namely by providing understanding to the community starting from identifying species, benefits and monitoring or data collection. The purpose of this service activity is to provide understanding to the community regarding seagrass ecology which includes types, benefits, status and threats as well as monitoring the condition of seagrass ecosystems. The method used in this service is in the form of counseling by resource persons and discussions regarding the role of seagrass ecosystems and the damage they face, as well as how to monitor seagrass cover. The results of the community service activities show that the community is very enthusiastic about being actively involved in efforts to manage seagrass ecosystems and monitoring results show that seagrass conditions at the location are included in the less rich category with a percentage of 37.5% with the highest percentage of species cover shown by Enhalus acoroides and Thalassia hemprichii. It is necessary to carry out transplant activities which are an effort to overcome the problem of the condition of the seagrass ecosystem in Mutiara Beach so that the function of the seagrass ecosystem can be ecologically sustainable, considering that the seagrass ecosystem in the area provides economic services to the people in the coastal area of Mutiara Beach. Service activities are very beneficial to the community, and have changed their mindset such as their understanding and awareness.